2018
DOI: 10.1097/prs.0000000000004312
|View full text |Cite
|
Sign up to set email alerts
|

Improved Long-Term Volume Retention of Stromal Vascular Fraction Gel Grafting with Enhanced Angiogenesis and Adipogenesis

Abstract: Stromal vascular fraction gel has a high long-term retention rate and a unique adipose regeneration mode, involving prompt inflammation and infiltration of immune cells, stimulating rapid angiogenesis and inducing host cell-mediated adipogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…Recent studies by other groups provide strong support for the hypothesis that when fat grafting is successful, this is explained by graft remodelling by stem cells rather than by adipocyte survival (Doi et al, 2015;Dong et al, 2015;Eto et al, 2012;Kato et al, 2014;Zhang et al, 2018). Furthermore, we have reported that the vast majority of grafted adipocytes dies when human fat grafts are implanted in a flow-through chamber model or subcutaneously in the scalp (Tang et al, 2018) in mice and yet new fat growth was seen in each case that was largely host derived.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…Recent studies by other groups provide strong support for the hypothesis that when fat grafting is successful, this is explained by graft remodelling by stem cells rather than by adipocyte survival (Doi et al, 2015;Dong et al, 2015;Eto et al, 2012;Kato et al, 2014;Zhang et al, 2018). Furthermore, we have reported that the vast majority of grafted adipocytes dies when human fat grafts are implanted in a flow-through chamber model or subcutaneously in the scalp (Tang et al, 2018) in mice and yet new fat growth was seen in each case that was largely host derived.…”
supporting
confidence: 55%
“…It is becoming increasingly clear from a number of recent studies that if there is adipocyte survival in grafted fat, this is restricted to the very outermost (100-300 μm) layer (Doi et al, 2015;Dong et al, 2015;Eto et al, 2012;Kato et al, 2014;Tang et al, 2018;Zhang et al, 2018), termed the "survival zone" (Eto et al, 2012). We were unable to identify such a zone in our constructs, and indeed, both adipocytes and adipose-derived stem cells (ASCs; discussed below) throughout the graft showed very poor survival.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…After centrifugation, we found that the processed lipoaspirates were separated into four parts (from top to bottom: lipid portion, lipid-devoid adipose tissue, liquid portion, and cell/tissue debris). The lipid-devoid adipose tissue, namely, extracellular matrix/stromal vascular fraction gel (SVF-gel), was found to have therapeutic ability in inducing angiogenesis and adipogenesis in vivo [20][21][22][23][24]. Unfortunately, the study of the liquid portion acquired from these physically processed lipoaspirates has been ignored.…”
Section: Introductionmentioning
confidence: 99%